2019
DOI: 10.1515/jpem-2018-0446
|View full text |Cite
|
Sign up to set email alerts
|

Maturity onset diabetes of the young (MODY) in Chinese children: genes and clinical phenotypes

Abstract: Background To investigate the clinical and molecular characteristics of Chinese children with maturity onset diabetes of the young (MODY). Methods A total of 42 Chinese patients suspected MODY referred to our unit from 2014 to 2018 were enrolled. Mutational analysis of monogenic diabetes mellitus genes was performed by next-generation sequencing and confirmed by Sanger sequencing. Results There were 28 males (66.7%) and 14 females (33.3%) with a mean age of 9.49 ± 3.46 years (range, 1.4–15.3 years) and a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…HNF1A-MODY even accounts for 52% of all MODY in the UK 7 . The detection rate of HNF1A-MODY was 14.3% (1/7 MODY patients) in the present cohort, which was higher than that of another Chinese study (1/28 MODY patients) 12 ; however, it was lower than that reported by a Korean study (3/14 MODY patients) 13 . Therefore, HNF1A-MODY appears to be uncommon in Chinese cohorts of children and adolescents with diabetes/persistent hyperglycemia.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…HNF1A-MODY even accounts for 52% of all MODY in the UK 7 . The detection rate of HNF1A-MODY was 14.3% (1/7 MODY patients) in the present cohort, which was higher than that of another Chinese study (1/28 MODY patients) 12 ; however, it was lower than that reported by a Korean study (3/14 MODY patients) 13 . Therefore, HNF1A-MODY appears to be uncommon in Chinese cohorts of children and adolescents with diabetes/persistent hyperglycemia.…”
Section: Discussioncontrasting
confidence: 87%
“…Another study identified 25 out of 42 Chinese patients with suspected MODY as having pathogenic or likely pathogenic variants, and 15 patients (60.0%, 15/25) with a GCK mutation, which is consistent with a Korean report (50.0%, 7/14). However, the Chinese study reported 36.0% of the mutations as novel, suggesting a unique mutation distribution in China 12,13 . As the rate and type of genetic mutations, as well as the presence of uncharacteristic clinical features associated with diabetes/persistent hyperglycemia, vary among different populations, it is necessary to define the genetic etiology associated with diabetes in children and adolescents in China further.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the widely used American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP) standards and guidelines (5) classifies only nine of these 88 variants as likely pathogenic or pathogenic variants that would be reported by our clinical diagnostic laboratory as likely causative of the patients' diabetes. This is not an isolated occurrence; other published research studies with an overreliance on in silico prediction tools have reported high levels (~90%) of false positive "likely pathogenic" monogenic diabetes variants (1)(2)(3). We have seen clinical diagnostic reports from laboratories in eight coun-tries across Europe, Asia, the Middle East, and the United States that have similarly reported such variants as incorrectly likely causative of a patient's diabetes.…”
Section: Prediction Algorithms In Genomic Medicinementioning
confidence: 86%
“…Recently published examples involving monogenic diabetes demonstrate how pathogenicity prediction algorithms can be very inaccurate for predicting which genetic variants are likely causal of dominant monogenic disease (1)(2)(3)(4). Here, we highlight the potential pitfalls of variant classification and how they can be avoided.…”
Section: Prediction Algorithms In Genomic Medicinementioning
confidence: 93%
“…The most common types of MODY were reported as MODY2 and MODY3 in many studies in populations other than Iran. [ 38 ] However, there are few studies on MODY to provide data concerning the frequency of different types of MODY in Iran. Moghbeli et al , in 2017 reported that among 34 Iranian families of MODY patients, only 2% of them harbored mutations in HNF1A gene.…”
Section: Discussionmentioning
confidence: 99%